Efektivitas Pembelajaran Hiybrid Learning Masa Pandemi Covid-19 Pada Mata kuliah IPA Kelas Rendah - Zainudin Zainudin*; Rica Wijayanti; Ria Faulina (JIPI (Jurnal IPA dan Pembelajaran IPA), 2021)
This research is a pre-experimental study, namely the application of hybrid learning during the COVID-19 pandemic in low-grade science courses. The research subjects were 28 fourth semester students for the 2020-2021 academic year, STKIP PGRI Bangkalan PGSD Study Program. The design used is One Group Pretest Posttest Design. The purpose of the study was to describe hybrid learning during the COVID-19 pandemic in low-grade science courses. The results of the study, namely scientific skills experienced a significant increase in the medium category. The results of student responses to hybrid learning during the COVID-19 pandemic in the Low Grade Science course were positive. It can be said that hybrid learning during the COVID-19 pandemic in low-grade science courses is effective